INNOVATIONS IN SMART ACCOUNTING SYSTEMS TO ACHIEVE EFFICIENCY AND ACCURACY IN FINANCIAL MANAGEMENT - Sifaul Anwar; Retno Paryati; Luis Santos (Yayasan Adra Karima Hubbi, 2026)
The massive growth of digital technology has had a significant impact on financial management systems and accounting practices across various types of organizations. Conventional accounting models that still rely on manual processes often face various challenges, including a high potential for errors in transaction recording, slow preparation of financial statements, low operational effectiveness, and limitations in generating timely and relevant information to support decision-making. This study aims to evaluate the role of intelligent accounting systems in improving the quality of financial management, particularly regarding the efficiency of work processes and the accuracy of the financial information generated. The approach used in this study is a literature review employing qualitative methods, drawing from various academic sources such as scientific articles, reference books, research reports, and other relevant documents discussing the development of contemporary accounting technology. The results of the study indicate that the implementation of such systems is capable of optimizing financial administration processes through the automation of various accounting activities, accelerating data processing and presentation, reducing the risk of errors caused by human factors, and enhancing transparency and accountability in financial management. Thus, the implementation of a smart accounting system can serve as an innovative solution that plays a crucial role in achieving financial management that is more efficient, reliable, and responsive.